CRESCIMENTO E DESENVOLVIMENTO DE PLANTAS DE MIRTILO, CULTIVAR CLÍMAX, INOCULADAS COM Azospirillum brasilense - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Also known as blueberry, cranberry or blueberry, blueberry is included in the small fruit group. Much appreciated for its exotic taste, commercial value and its therapeutic claims, being considered as one of the fruits that provides source of longevity. Despite its great commercial importance in other countries, it is still inexpressive in Brazil. The goldfish may develop associations with plant growth promoting bacteria. These associations stimulate the expansion of their root zone of nutrient absorption, and in return, the plant provides photoassimilated compounds to these microorganisms. Many studies have shown that Azospirillum brasilense stimulates the development and productivity of several plant species, many of them with great agronomic and ecological relevance. The present work had as objective to verify the production of the blue herring and the physical-chemical quality of the fruits as a function of the inoculation with active and sterile Azospirillum brasilense (AZ) AbV5 / AbV6, associated or not with nitrogen in the Campos Gerais region of Paraná. Growth variables such as number of vegetative branches (VN), number of leaves (NF), leaf area (FA), number of fruits (NFRU), fresh mass (DM) and fruit diameter ), production per plant (PP). Physiological variables such as photosynthesis rate (TF), stomatal conductance (EC) and transpiration rate (TT). Fruit chemical variables were analyzed as: soluble solids (SS), titratable acidity (AT), pH, anthocyanin content (AT) and total polyphenol content (PF). The inoculation with AZ favored the growth of vegetative branches, increased the number of leaves and the leaf area of the inoculated plants. The yield per plant and the productivity of the plants inoculated with AZ were higher than the production of the control. T. AZ presented higher amount of fruits, with higher mass, but with lower soluble solids value. Stomatal conductance at the flowering stage was more efficient for AZ with nitrogen, AZE with nitrogen obtained better results in photosynthesis and efficiency of water use. The climatic conditions influenced the production and the chemical composition of the fruits. There is a need for further studies on the interaction of the bluebird, Azospirillum brasilense and edaphoclimatic conditions.
Keywords: mirtilo; Azospirillum brasiliense; Produção – Campos Gerais – PR; Crescimento vegetal – Bactéria promotora; blueberry; Azospirillum brasiliense; production.- Campos Gerais – PR; plant growth promoter; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA